Effect of Menstrual Hygiene Education Based on Peer and Small Group Teaching Methods on Hygiene Behaviors in Female Adolescents: A Comparative Study - Reihaneh Jarrahi; Nahid Golmakani; Seyed Reza Mazlom (Mashhad University of Medical Sciences, 2020)
Menstrual hygiene education in adolescence is an important factor to prevent fertility problems. The present study aimed to compare the effect of menstrual hygiene education based on peer and small group teaching methods on hygiene behaviors in female adolescents. This randomized controlled clinical trial was performed on 90 high school students in 2018. Three high schools in Mashhad, Iran, were allocated to three groups by drawing lots. The peers and small groups were provided with educational content within a month and over four sessions, respectively. Moreover, the control group received routine education. The data were collected by a researcher-made questionnaire before and after the intervention and analyzed by SPSS software (version 16) using the analysis of variance, as well as Chi-square and Kruskal-Wallis tests. According to the Kruskal-Wallis test, the three groups were homogeneous regarding age (P=0.12). Furthermore, the mean scores of hygiene behaviors in the intervention groups (after the intervention) were significantly higher than in the control group (P<0.001) and higher in the peers than in the small groups (P<0.001). It is recommended to employ peer teaching on menstrual hygiene by health planners.